Transcription - Atkinson, Kate (Little, Brown and Company, 2018)
In 1940, eighteen-year old Juliet Armstrong is reluctantly recruited into the world of espionage. Sent to an obscure department of MI5 tasked with monitoring the comings and goings of British Fascist sympathizers, she discovers the work to be by turns both tedious and terrifying. But after the war has ended, she presumes the events of those years have been relegated to the past forever. Ten years later, now a radio producer at the BBC, Juliet is unexpectedly confronted by figures from her past. A different war is being fought now, on a different battleground, but Juliet finds herself once more under threat. A bill of reckoning is due, and she finally begins to realize that there is no action without consequence.